Crimean-Congo hemorrhagic fever: History, epidemiology, pathogenesis, clinical syndrome and genetic diversity - Bente, Dennis A.; Forrester, Naomi L.; Watts, Douglas M.; McAuley, Alexander J.; Whitehouse, Chris A.; Bray, Mike (Antiviral research, 2013)
•Crimean–Congo hemorrhagic fever (CCHF) is the most widespread tick-borne viral disease of humans.•Its incidence in Turkey and Iran has markedly increased in the past decade.•The broad sequence diversity of the virus reflects prolonged genetic drift and reassortment between strains.•Until recently, vaccine and drug development have been hindered by the lack of animal models.•Research is needed to develop effective countermeasures against CCHF. Crimean–Congo hemorrhagic fever (CCHF) is the most important tick-borne viral disease of humans, causing sporadic cases or outbreaks of severe illness across a huge geographic area, from western China to the Middle East and southeastern Europe and throughout most of Africa. CCHFV is maintained in vertical and horizontal transmission cycles involving ixodid ticks and a variety of wild and domestic vertebrates, which do not show signs of illness. The virus circulates in a number of tick genera, but Hyalomma ticks are the principal source of human infection, probably because both immature and adult forms actively seek hosts for the blood meals required at each stage of maturation. CCHF occurs most frequently among agricultural workers following the bite of an infected tick, and to a lesser extent among slaughterhouse workers exposed to the blood and tissues of infected livestock and medical personnel through contact with the body fluids of infected patients. CCHFV is the most genetically diverse of the arboviruses, with nucleotide sequence differences among isolates ranging from 20% for the viral S segment to 31% for the M segment. Viruses with diverse sequences can be found within the same geographic area, while closely related viruses have been isolated in far distant regions, suggesting that widespread dispersion of CCHFV has occurred at times in the past, possibly by ticks carried on migratory birds or through the international livestock trade. Reassortment among genome segments during co-infection of ticks or vertebrates appears to have played an important role in generating diversity, and represents a potential future source of novel viruses. In this article, we first review current knowledge of CCHFV, summarizing its molecular biology, maintenance and transmission, epidemiology and geographic range. We also include an extensive discussion of CCHFV genetic diversity, including maps of the range of the virus with superimposed phylogenetic trees. We then review the features of CCHF, including the clinical syndrome, diagnosis, treatment, pathogenesis, vaccine development and laboratory animal models of CCHF. The paper ends with a discussion of the possible future geographic range of the virus. For the benefit of researchers, we include a Supplementary Table listing all published reports of CCHF cases and outbreaks in the English-language literature, plus some principal articles in other languages, with total case numbers, case fatality rates and all CCHFV strains on GenBank.